A short history of modern philosophy : from Descartes to Wittgenstein - Scruton, Roger (Routledge, 1995)
This new edition of Roger Scruton's widely acclaimed Short History covers all the major thinkers in the Western tradition, from Descartes to Wittgenstein. It is an ideal introduction to philosophical history for all those with an interest in this fascinating subject.